Serological testing for infectious diseases in pregnant women: are the guidelines followed? (Swiss Medical Weekly, 2011)
QUESTIONS: Are the guidelines for serological testing in pregnancy followed, and are the results on hand on admission to the labour ward? METHODS: From 1.1.2007 to 31.12.2007, all patients’ records were checked for serological analyses on admission to the labour ward. The serologies tabulated included tests for rubella, toxoplasmosis, hepatitis B, syphilis, HIV, varicella, cytomegalovirus infection (CMV) and parvovirus B19. RESULTS: A total of 723 pregnant women were included. Rubella and toxoplasmosis serologies were missing in 1.66% of cases, hepatitis B in 2.77%, syphilis in 12.72%, and HIV in 30.57%. Serological testing for varicella, CMV and parvovirus B19 were carried out in only about 10% of patients. We found that 95.81% of Swiss/Austrian/German patients were immune to rubella compared to 89.59% for patients from other origins. A total of 50.0% of Swiss/Austrian/German patients and 27.44% of patients from other origins were immune to toxoplasmosis. As for hepatitis B antibodies (0.25 vs. 1.26%) and syphilis (only 1 patient tested positive), no significant differences were found. HIV tests were negative for all patients. CONCLUSIONS: To sum up, in our collective, serologic testing for rubella, toxoplasmosis and hepatitis B is carried out in almost all pregnant women. The high rate of women not screened for HIV infection clearly contradicts the recommendations of the Federal Office of Public Health and calls for increased education of physicians.